2013
DOI: 10.4103/0972-0707.105299
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic dental pulp calcifications in a tertiary care setting in South India

Abstract: Background:Dental pulp calcifications are unique and represent the dental pulp regenerative process. Dental pulp calcifications are sometimes routine findings in oral radiographs and may later serve as an important diagnostic criterion for a hidden aspect of systemic illness.Objective:The purpose of this study was to assess the patterns and prevalence of idiopathic dental pulp calcifications in a tertiary care setting in South India.Materials and Methods:A total of 227 patients were included in the study fulfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 14 publications
4
20
1
3
Order By: Relevance
“…As reported previously, age-dependent narrowing of the pulp canal results in calcification of DP tissue [10]. In the age group of 50-60 years, we also observed very low amount of DP and MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…As reported previously, age-dependent narrowing of the pulp canal results in calcification of DP tissue [10]. In the age group of 50-60 years, we also observed very low amount of DP and MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…More than half of the primary studies reported higher prevalences of pulp stones among women . That was the case for the total estimate.…”
Section: Discussionmentioning
confidence: 84%
“…During a comprehensive search, 952 studies were identified. After a sequential screening (duplicate exclusion, review of titles, abstracts and full texts), 5 case‐control studies, 1 review literature and 8 studies due to not reporting prevalence were excluded. The remaining 16 papers were quality assessed all of which had high to moderate quality scores and were considered eligible for meta‐analysis (Figure and Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The present study concluded that there is the need for new studies with large numbers of subjects and different populations to find a correlation between pulp stone and cardiovascular diseases. Satheeshkumar et al [19]. Investigated idiopathic pulpal calcifications in Southern India.…”
Section: Discussionmentioning
confidence: 99%